Inclusion of the excited states quark propagator to the nucleon electromagnetic form factors in the perturbative chiral quark model - J. Jarassriwilai (Results in Physics, 2020)
Electromagnetic form factors of the nucleon are studied within the framework of the Perturbative Chiral Quark Model (PCQM). In a previous analysis of the nucleon electromagnetic form factors, the quark propagator used in the calculation was truncated to quark in the ground state only. The attempt to include the excited states quark propagator contribution to the neutron was performed but not on the proton. Therefore, in this work, we try to be consistent in the nucleonic sector by including the excited states quark propagator up to the second excited states to study the electromagnetic form factors of the nucleon. Our results are in good agreement with experimental data and show the significance of the contribution of the quark excited states propagator to the electromagnetic properties of the nucleon.